Alkylsulfanylphenyl derivatives of cytosine and 7-deazaadenine nucleosides, nucleotides and nucleoside triphosphates: synthesis, polymerase incorporation to DNA and electrochemical study - Macíčková-Cahová, Hana; Pohl, Radek; Horáková, Petra; Havran, Luděk; Špaček, Jan; Fojta, Miroslav; Hocek, Michal (Chemistry (Weinheim an der Bergstrasse, Germany), 2011)
Aqueous Suzuki-Miyaura cross-coupling reactions of halogenated nucleosides, nucleotides and nucleoside triphosphates derived from 5-iodocytosine and 7-iodo-7-deazaadenine with methyl-, benzyl- and tritylsufanylphenylboronic acids gave the corresponding alkylsulfanylphenyl derivatives of nucleosides and nucleotides. The modified nucleoside triphosphates were incorporated into DNA by primer extension by using Vent(exo-) polymerase. The electrochemical behaviour of the alkylsulfanylphenyl nucleosides indicated formation of compact layers on the electrode. Modified nucleotides and DNA with incorporated benzyl- or tritylsulfanylphenyl moieties produced signals in [Co(NH(3))(6)](3+) ammonium buffer, attributed to the Brdička catalytic response, depending on the negative potential applied. Repeated constant current chronopotentiometric scans in this medium showed increased Brdička catalytic response, which suggests the deprotection of the alkylsulfanyl derivatives to free thiols under the conditions.
Keywords: DNA-Directed DNA Polymerase; Molecular Structure; Nucleosides; Base Sequence; Cytosine; molekulární struktura; Nucleotides; Polyphosphates; DNA-dependentní DNA-polymerasy; cytosin; sulfhydrylové sloučeniny; polyfosfáty; nukleotidy; Electrochemistry; Sulfhydryl Compounds; nukleosidy; sekvence nukleotidů; elektrochemie